Searching for Optimal Control Parameters of Thermal Object Using Pulse-Width Modulation (PWM) Control with Predictive Filter - Yevseienko, Oleg; Gapon, Anatoliy; Salnikov, Dmytro (Lviv Polytechnic Publishing House, 2015)
The thesis is devote to the temperature control of objects with lumped or distributed parameters. The problems of choosing the right value of regulator’s heater power and prediction period are discussed. The major attention is paid to the process of searching the minimum value of control quantities. It is shown that the approximated second-order plane has an exact accordance with the original data. It is concluded that algorithm of PWM-control with prediction filter provides good quality control.
Keywords: distributed parameters; lumped parameters; transient function; dead-time; temperature control